EU-wide networking: An instrumental valuable for European rural development policies in Romania? - Doris Marquardt; Judith Möllers; Gertrud Buchenrieder (European Countryside, 2009)
This paper examines the relevance of networking as an instrument for implementing European rural development policies. The LEADER programme of the European Union (EU) supports partnerships and networking within and between rural regions in the EU and aims at advancing rural, regional socio-economic development. LEADER and the establishment of the European and National Networks for Rural Development, respectively, are discussed using the example of the case of Romania, where these measures are currently implemented. The discussion is primarily based on results of 2008 surveys among various stakeholders involved in LEADER in Romania, Hungary and Germany. We conclude that networking is a key factor for successfully implementing rural development policies. This is due to benefits resulting from the exchange of experiences or partnerships, but also due to social control - a hidden effect of networking. – – Dieser Beitrag befasst sich mit der Bedeutung von Netzwerken als Instrument zur Umsetzung der europäischen Politik zur Entwicklung des Ländlichen Raums. Durch das EU-Programm LEADER werden Partnerschaften und Netzwerkaktivitäten in und zwischen ländlichen Regionen unterstützt mit dem Ziel einer Förderung ihrer sozioökonomischen Entwicklung. LEADER sowie der Aufbau des Europäischen und des Nationalen Netzwerks für den Ländlichen Raum werden im Hinblick auf die Situation in Rumänien diskutiert, wo derzeit diese Maßnahmen eingeführt werden. Der Beitrag stützt sich vor allem auf Ergebnisse von im Jahr 2008 durchgeführten Umfragen unter am LEADER Programm beteiligten Personen in Rumänien, Ungarn und Deutschland. Es zeigt sich, dass Netzwerke ein Schlüsselfaktor für die Implementierung ländlicher Entwicklungspolitik sind. Es spielt dabei nicht nur der erwartete Nutzen durch Erfahrungsaustausch und Partnerschaften eine Rolle, sondern auch soziale Kontrolle, welche als verdeckter Effekt von Netzwerken zu sehen ist.
Keywords: 330; rural development policies; LEADER; European Network for Rural Development; networking; Romania; Politik zur Entwicklung des ländlichen Raums; Europäisches Netzwerk für ländliche Entwicklung; Netzwerke; Rumänien